2021
DOI: 10.1186/s43166-021-00076-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between smoking, clinical, inflammatory, and radiographic parameters in patients with ankylosing spondylitis

Abstract: Background Ankylosing spondylitis (AS) is an autoimmune multisystemic disease that attacks the spine, sacroiliacs, and often causes asymmetrical peripheral oligoarthritis. It results from the interaction between the genetic factors mainly Human Leukocyte Antigen B27 (HLA B27) and environmental factors. Current smoking has been reported to be a major risk factor for the incidence and progression of ankylosing spondylitis. So, we aim to explore the relationship between smoking and each of the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“… 10 The different studies have shown that patients who smoke have an early onset of the disease and higher spinal pain, disease activity, functional impact and radiographic progression compared with non-smokers, as well as a lower response to anti-TNF drugs. 11 Similarly, smoking increases cardiovascular risk and may worsen cardiovascular and pulmonary comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“… 10 The different studies have shown that patients who smoke have an early onset of the disease and higher spinal pain, disease activity, functional impact and radiographic progression compared with non-smokers, as well as a lower response to anti-TNF drugs. 11 Similarly, smoking increases cardiovascular risk and may worsen cardiovascular and pulmonary comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking is associated with increased cumulative spinal structural damage in patients with AS [87] as well as higher disease activity, inflammatory markers and functional disability [88]. Whether smoking induces AS is unclear.…”
Section: Diet and Lifestyle Factorsmentioning
confidence: 99%